Efficiency Rainwater Harvesting at the Roof Campus Buildings - C S Silvia; M Ikhsan; M Safriani; T P Gusmilia (International Journal of Engineering, Science and Information Technology, 2021)
Rainwater harvesting is implemented appropriately by striving to use costs that are quite cheap and efficient, but still has many benefits for meeting clean water needs. In this study, the rainwater harvesting model to be analyzed was using the cistern method. The advantage is that it is easier to apply, the amount of water collected is quite large, and it does not require a large area of land. By implementing a culture of harvesting rainwater, can get several benefits, including reducing runoff which can prevent the UTU campus area from inundation and flooding. The average volume of rainwater that can be harvested using a 5-year return period is 110581.12 liter/day with an average volume of water requirements of 7452.09 liters/day. From the results of the rainwater harvesting analysis, it can be concluded that this method is capable of being applied where the analysis results show that the harvested rainwater can meet the water needs of users on the Teuku Umar University campus. In the future, it will be planning where the excess water stored in the cistern will be channeled into infiltration wells to maintain groundwater sources sustainably.